Multiple colonization of Madagascar and socotra by colubrid snakes: evidence from nuclear and mitochondrial gene phylogenies - Nagy, Zoltán Tamás; Wink, Michael (Proceedings of the Royal Society of London. Series B, Biological sciences, 2003)
Colubrid snakes form a speciose group of unclarified phylogeny. Their almost cosmopolitan distribution could be interpreted as a product of plate-tectonic vicariance. We used sequences of the nuclear c-mos, the mitochondrial cytochrome b and the 16S rRNA genes in 41 taxa to elucidate the relationships between the endemic colubrid genera found in Madagascar and in the Socotra archipelago. The well-resolved trees indicate multiple origins of both the Malagasy and the Socotran taxa. The Malagasy genus Mimophis was nested within the Psammophiinae, and the Socotran Hemerophis was closely related to Old World representatives of the former genus Coluber. The remaining 14 genera of Malagasy colubrids formed a monophyletic sister group of the Socotran Ditypophis (together forming the Pseudoxyrhophiinae). Molecular-clock estimates place the divergence of Malagasy and Socotran colubrids from their non-insular sister groups into a time-frame between the Eocene and Miocene. Over-seas rafting is the most likely hypothesis for the origin of at least the Malagasy taxa. The discovery of a large monophyletic clade of colubrids endemic to Madagascar indicates a need for taxonomic changes. The relationship of this radiation to the Socotran Ditypophis highlights the potential of the Indian Ocean islands to act as an evolutionary reservoir for lineages that have become extinct in Africa and Asia.
Gesehen am 04.10.2017